A model for cross-institutional collaboration: how the intercollegiate biomathematics alliance is pioneering a new paradigm in response to diminishing resources in academia. Issue 1 (14th December 2018) - Akman, Olcay; Powell, Megan
Abstract: We present an emerging model of shared academic, intellectual and infrastructure resources that addresses the need for institutions to sustain their educational and scholarship missions under ever-declining funding. The (IBA) was created in 2014 by Illinois State University for this purpose, eventually growing to a state-recognized 'Center for Collaborative Studies' in 2017. As the impact of the IBA continues to expand, it is on its way to become a new education paradigm in response to diminishing resources, and it can serve as a model to foster collaboration for other fields of mathematics.